2022
DOI: 10.3390/membranes12030338
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction and Internal Heating Effects on the Double Diffusive Convection in Porous Membrane Enclosures Soaked with Maxwell Fluid

Abstract: In this paper, the joint impact of the interior heating and chemical reaction on the double diffusive convective flow in porous membrane enclosures soaked by a non-Newtonian Maxwell fluid is investigated applying linear and nonlinear stability techniques. The porous enclosures are square, slender and rectangular. Using the linear stability analysis, the expression for the critical thermal Rayleigh–Darcy number, above which the convective movement occurs, is derived analytically in terms of associated physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Mainly, the mathematical model of the concentration changes [33] can been improved in considering the proposed model's fractional origin. This also makes it possible to improve practical ways for ensuring the reliability of the linear fractional advection-diffusion, advection-dispersion, and convection-dispersion models [35], i.e., through heteroporous membranes [36,37]. It also allows for improving the pneumatic classification process for granular material in rhomb-shaped The following parameters have been identified after p = 9 approximation cycles: γ = 0.587 and κ = 0.301.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, the mathematical model of the concentration changes [33] can been improved in considering the proposed model's fractional origin. This also makes it possible to improve practical ways for ensuring the reliability of the linear fractional advection-diffusion, advection-dispersion, and convection-dispersion models [35], i.e., through heteroporous membranes [36,37]. It also allows for improving the pneumatic classification process for granular material in rhomb-shaped The following parameters have been identified after p = 9 approximation cycles: γ = 0.587 and κ = 0.301.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the Damkohler number has a contrast effect on steady and oscillatory convection. Yadav et al [19] extended the work done by Reddy and Ragoju [15] by considering internal heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar Pundir et al [24] investigated the linear stability of a fuid layer with nanoparticles in the presence of a solute gradient. Using linear and nonlinear stability approaches, Yadav et al [25,26] investigated the combined infuence of heating and chemical reaction on the doubledifusive convective in a non-Newtonian Maxwell fuid and Kuvshiniski type saturated porous layer. Tey determined that oscillatory convection is only possible when the solute Rayleigh-Darcy number is negative and that it is also infuenced by other physical factors.…”
Section: Introductionmentioning
confidence: 99%